Study of the Concept of Asylum in the View of Islam and International Law - Mohsen Ghadir; Hossein kazemi (پژوهش تطبیقی حقوق اسلام و غرب, 2018)
Although both Islamic jurisprudence and international sources have recognized certain rights for refugees, the concept of asylum and definition of refugee in Islam differ from those of international instruments. Phenomenon of asylum, analogous to having a broad range in terms of history and legal development in international law, has been accepted and possess a specific and distinguished position in Islam as well so that from the beginning of the establishment of Islamic state and even prior to advent of Islam, the tradition of asylum and protection of refugees had existed and have had a religious form. Asylum is called Amān in Islamic jurisprudence. Being universal and toward the humanity as a whole, the view of Islam regarding rights of refugees is not a religious and exclusive one. Asylum entered into international treaties through the conclusion of the 1951 Convention relating to the Status of Refugees. Under international law, asylum is substantially of a recommendatory nature and has no strong guarantee along with an international mechanism. More or less, he rights and duties of refugees in Islam and international law are similar and due to the fact that Amān is a contract, the Islamic state can, subject to not being contrary to prudence and divine law, accept the other conditions and rights of refugees as provisos. The present article, through an analytic method, aims at studying the rights of refugees in accordance to Islamic sources and international law comparatively.